Legal Support for the Reform of Ukraine’s Customs Service in the Context of European Integration - Cherkunov, Oleksandr (PRAWO i WIĘŹ, 2025)
Ukraine’s customs reform introduces ambitious personnel policy tools intended to modernize public service and align it with EU standards. This paper examines how the main reform tools affect the legal system – contractual service, staff rotation, competency assessment, and certification – focusing on their design, implementation, and alignment with European practices. While these tools are presented as instruments of anti-corruption and institutional efficiency, the study reveals that unclear rules and inflexible procedures may prevent these tools from working as intended. Drawing on comparative analysis and domestic case law, the paper highlights the legal uncertainty surrounding contract terms, the lack of appeal mechanisms in assessment procedures, and the risks of excessive managerial discretion. The findings suggest that without clearer rules, predictable processes, and a stronger rights-based framework, the reform may compromise motivation, fairness, and sustainability in Ukraine’s customs administration.